1979
DOI: 10.1042/bj1770861
|View full text |Cite
|
Sign up to set email alerts
|

Multiple inhibition of glutathione S-transferase A from rat liver by glutathione derivatives: kinetic analysis supporting a steady-state random sequential mechanism

Abstract: Glutathione derivatives inhibit glutathione S-transferase A [cf. Biochem. J. (1975) 147, 513--522]. The steady-state kinetics of this inhibition have been investigated in detail by using S-octyglutathione, glutathione disulphide and S-(2-chloro-4-nitrophenyl)glutathione: the last compound is a product of the enzyme-catalused reaction. Interpreted in terms of generalized denotations of inhibition patterns, the compounds were found to be competitive with the substrate glutathione. Double-inhibition experiments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

1981
1981
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 10 publications
3
22
0
1
Order By: Relevance
“…However, there is a lack of agreement as to whether mammalian GSTs exhibit rapid-equilibrium or steady-state kinetics. In some cases, the random, rapid-equilibrium model provided the best fit to the data (Schramm et al, 1984;Ivanetich and Goold, 1989;Young and Briedis, 1989;Phillips and Mantle, 1991), whereas in others the kinetics were best described by the random, steady-state model (Jakobson et al, 1979;Ivanetich et al, 1990). It has been suggested Figure 10.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is a lack of agreement as to whether mammalian GSTs exhibit rapid-equilibrium or steady-state kinetics. In some cases, the random, rapid-equilibrium model provided the best fit to the data (Schramm et al, 1984;Ivanetich and Goold, 1989;Young and Briedis, 1989;Phillips and Mantle, 1991), whereas in others the kinetics were best described by the random, steady-state model (Jakobson et al, 1979;Ivanetich et al, 1990). It has been suggested Figure 10.…”
Section: Discussionmentioning
confidence: 99%
“…Bireactant models have been used to characterize the kinetic mechanisms of mammalian GSTs (Jakobson et al, 1979;Schramm et al, 1984;Ivanetich and Goold, 1989;Young and Briedis, 1989;Ivanetich et al, 1990;Phillips and Mantle, 1991). For mammalian GSTs, analyses of initialvelocity data with bireactant kinetic models have indicated that the kinetic mechanism is random and sequential.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 5 in Jakobson et al, 1979). Proper units of the parameters can be deduced by considering that the standard error is expressed in /SM/min and the reactant concentrations in mm (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The residuals obtained after fitting a suitable rate equation (see Fig. 5 in Jakobson et al, 1979) were divided into groups of six (as indicated by boxes in Fig. 5 of the present paper) and the local variance was calculated for each group of points.…”
Section: Effect Of Weighting Factors On Parameter Estimationmentioning
confidence: 99%